"Uroptysis!" – A case report of xanthogranulomatous pyelonephritis with nephrobronchial fistulation. (September 2022) - O'Neill, S.; Motyer, R.; O'Neill, H.; Brennan, I.; Ryan, J.M.; Guiney, M.
Abstract: Introduction and importance: Xanthogranulomatous pyelonephritis (XGP) is an uncommon complication of chronic urinary tract infection, classically secondary to a chronic obstructive uropathy, resulting in destruction of renal parenchyma and a non-functioning kidney (Jha and Aeddula, 2022 [1]). This is rarely associated with nephrobronchial fistulation, with few published case reports in the literature to date. Case presentation: We present the rare case of a 42-year-old female who was admitted to an Irish tertiary urology centre with abdominal pain, elevated inflammatory markers and an obstructive uropathy on initial imaging, with a new diagnosis of XGP. Initial management was with targeted intravenous antimicrobial therapy, percutaneous nephrostomy and perinephric drain insertion. The subsequent discovery of a nephrobronchial fistula later complicated the case, warranting plan for interval nephrectomy and fistula repair following prolonged medical management. We discuss the initial presentation, workup and image-guided approach to management. Clinical discussion: XGP is an uncommon sequela of chronic renal suppurative infection, and is usually associated with long-standing ureteric obstruction secondary to a staghorn calculus. Nephrobronchial fistulation is a rare complication of XGP, highlighting the significance of this case discussion. Conclusion: XGP should be considered in cases of suspected chronic pyelonephritis and may rarely lead to nephrobronchial fistulation. In cases of known XGP and pleural empyema, nephrobronchial fistulation should be considered as part of the differential diagnosis. Highlights: Xanthogranulomatous pyelonephritis is rare and associated with chronic upper urinary tract infection and obstruction. Nephrobronchial fistulation is a rare complication of xanthogranulomatous pyelonephritis. In cases of XGP and concurrent pleural empyema, a nephrobronchial fistula should be considered.